Design and Performance Analysis of GPON-Based FTTH Network in Sikucur Barat Padang Pariaman Regency - Uzma Septima; Rikki Vitria; Ratna Dewi; Ramiati Ramiati; Yola Febrilla (Brilliance: Research of Artificial Intelligence, 2026)
The increasing demand for internet services requires broadband infrastructure capable of providing high-capacity and reliable connectivity, including in rural areas. Nagari Sikucur Barat, Padang Pariaman Regency, requires an optical access network to support the growing communication needs of the community. This study aims to design and evaluate the performance of a Fiber To The Home (FTTH) network based on Gigabit Passive Optical Network (GPON) technology. The research applies the Prepare, Plan, Design, Implement, Operate, and Optimize (PPDIOO) methodology through geographical analysis, network planning using Google Earth Pro and AutoCAD, OptiSystem simulation, and performance evaluation based on Link Power Budget, Rise Time Budget, Q-Factor, and Bit Error Rate (BER). The proposed network serves 88 homepasses using 3 PON ports, 13 Optical Distribution Points (ODPs), 4 PLC 1:4 splitters, and 13 distribution splitters. The calculated attenuation ranges from 27.0523 dB to 27.2632 dB, with received power values between ?20.0523 dBm and ?20.2632 dBm and power margins ranging from 7.7368 dB to 7.9477 dB. Simulation results produce Q-Factor values of 12.1746 to 13.7883 and BER values of 1.49433 × 10??³ to 6.58298 × 10?³?, indicating compliance with GPON transmission quality requirements. The Rise Time Budget ranges from 0.3637 ns to 0.3712 ns, exceeding the theoretical limit of 0.29 ns. The results indicate that the proposed network is feasible for deployment because it satisfies the received power, power margin, Q-Factor, and BER requirements, while further optimization is needed to improve rise time performance.